What do patients experience? Interprofessional collaborative practice for chronic conditions in primary care: an integrative review - Davidson, Alexandra R.; Kelly, Jaimon; Ball, Lauren; Morgan, Mark; Reidlinger, Dianne P. (BMC family practice, 2022)
Background Improving the patient experience is one of the quadruple aims of healthcare. Therefore, understanding patient experiences and perceptions of healthcare interactions is paramount to quality improvement. This integrative review aimed to explore how patients with chronic conditions experience Interprofessional Collaborative Practice in primary care. Methods An integrative review was conducted to comprehensively synthesize primary studies that used qualitative, quantitative, and mixed methods. Databases searched were Medline, Embase, CINAHL and Web of Science on June 1st, 2021. Eligible studies were empirical full-text studies in primary care that reported experiences or perceptions of Interprofessional Collaborative Practice by adult patients with a chronic condition, in any language published in any year. Quality appraisal was conducted on included studies using the Mixed Method Appraisal Tool. Data on patients’ experiences and perceptions of Interprofessional Collaborative Practice in primary care were extracted, and findings were thematically analyzed through a meta-synthesis. Results Forty-eight ( n = 48) studies met the inclusion criteria with a total of n = 3803 participants. Study quality of individual studies was limited by study design, incomplete reporting, and the potential for positive publication bias. Three themes and their sub-themes were developed inductively: (1) Interacting with Healthcare Teams, subthemes: widening the network, connecting with professionals, looking beyond the condition, and overcoming chronic condition collectively; (2) Valuing Convenient Healthcare, subthemes: sharing space and time, care planning creates structure, coordinating care, valuing the general practitioner role, and affording healthcare; (3) Engaging Self-care, subthemes: engaging passively is circumstantial, and, engaging actively and leading care. Conclusions Patients overwhelmingly had positive experiences of Interprofessional Collaborative Practice, signaling it is appropriate for chronic condition management in primary care. The patient role in managing their chronic condition was closely linked to their experience. Future studies should investigate how the patient role impacts the experience of patients, carers, and health professionals in this context. Systematic review registration PROSPERO: CRD42020156536.